2004
DOI: 10.1080/0376835042000219550
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between budget deficit and interest rates in South Africa: some econometric results

Abstract: This article investigates the budget deficit-interest rate relationships in South Africa, using two econometric methods: the London School and the Granger-causality methods. The results suggest that budget deficits have no effect on interest rates in South Africa. The causality results reinforce this finding by indicating that budget deficit and interest rates in this country are independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The author finds that budget deficits do not influence interest rates in South Africa. Uwilingiye and Gupta (2007) verify the claim made by Akinboade (2004) using Granger causality and cointegration analysis. The authors focused on the relationship between the short-term interest rate and budget deficits and found that the causal relationship between the shortterm interest rate and budget deficit depends on the periodicity of the data.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The author finds that budget deficits do not influence interest rates in South Africa. Uwilingiye and Gupta (2007) verify the claim made by Akinboade (2004) using Granger causality and cointegration analysis. The authors focused on the relationship between the short-term interest rate and budget deficits and found that the causal relationship between the shortterm interest rate and budget deficit depends on the periodicity of the data.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Several studies regarding budget deficits have been conducted by previous researchers. Arora and Dua (1993), Saleh (1996), Akinboade (2004), Bayar, and Smeets (2009) as well as Agnello, and Sousa ( 2009)examined budget deficits in the developed countries. These researchers used different data sets and applied different econometric methods, and therefore discovered assorted results.…”
Section: An Overview Of Literaturementioning
confidence: 99%
“…Table 2 shows that fiscal deficits do not influence the prime rate, which confirms the interest neutrality of budget deficits (Akinboade 2004;Barro 1989;Choi & Holmes 2014;Darrat 1989). Table 3 shows that budget deficits do not granger cause the prime rate.…”
Section: Vector Autoregressive Regression and Autoregressive Distribu...mentioning
confidence: 57%
“…A study of sub-Saharan African economies also found the Ricardian claim that interest rates are non-responsive or neutral to changes in fiscal deficits to hold (Kelikume 2016). Akinboade (2004) also found fiscal deficits to have no effect on interest rates in South Africa, while Bonga-Bonga (2012) found budget deficits to have a positive effect on long-term interest rates. Akinboade (2004) tested the relationship on all kinds of nominal interest rates and the relationship was robust.…”
Section: The Neoclassical Link Between Fiscal Deficit and Unemploymentmentioning
confidence: 99%
See 1 more Smart Citation